God may as well exist outside time. Regarding one big discussion in analytical metaphysics - Vladimir Shokhin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2020)
It was not up to the mid-20th century that timelessness of God had been a topic of discussions, bit now it is a hot issue in analytical metaphysics in which you can even distinguish “strong”, “moderate”, and “weak” positions of its proponents and opponents, the latter positions becoming more and more prevalent. Arguments proposed by both sides demonstrate strong sides of the analytical method, but the participants of this discussion are united by the circumstance that they believe to have access to God’s nature itself and not only to our opinions about it, thus exhibiting features of pre-Kantian thinking. This article, by contrast, proposes a solution to a more humble problem, i.e. the defi nition of which solution to the discussed question is coherent in the concrete religious world outlook, and the author puts forward logical (primarily, traditional from God’s inalterability) and illustrative arguments in favour of the assumption that the idea of Divine temporality accords well with pantheist world outlook, whereas it can be incorporated in the theistic only with a destructive eff ect for the latter. The article concludes with the assumption that the most coherent idea of God is Anselm’s identifi cation of God as something “more than which nothing can be thought of”, including the attribute of non-temporality, corresponding to classical theism, and the argument as to fact why despite this fact apanentheistic ideas become more and more popular in present-day Western philosophical theology.